Provisions of Applying Health Guidelines with regard to the Emerging of Corona Virus: A Comparative Jurisprudence Study (Islamic Sciences Journal, 2023)
ABSTRACT                This study examines the implementation of health recommendations in connection to corona virus and its current condition from an Islamic viewpoint. With the pandemic spreading around the world and no existing effective cure or ways to stop it except for following the preventative measures advised by the health agencies in each nation, the necessity for such study is essential. The goal of this study is to describe the origin of the Corona virus and general provisions related to it, including: the use of curfew during an outbreak of the virus, the departure and arrival of an infected country, receiving Corona vaccination, and elaborating on specific provisions concerning affected mosques that should be closed during an outbreak of the virus, social segregation between prayers, wearing masks during prayers, and finally provision concerning washing and burying affected corpses.  The researcher comes to the conclusion that national health policies are the same as Islamic law, which places a strong emphasis on maintaining the five requirements, including self-preservation.
Keywords: virus, corona, covid 19, immunization, medication